Promoting health and preventing malnutrition among children in rural Bangladesh: A qualitative study - Margareta Westerbotn; Felicia Monfors; Julia Reusser; Marie Tyrrell (Wiley, 2023)
Abstract Aim To describe community healthcare professionals' experiences of preventing malnutrition among children in rural Bangladesh. Methods A descriptive qualitative study with a total of seven healthcare professionals were recruited from a non‐governmental organisation in rural Bangladesh. Individual in‐depth interviews were conducted in November 2018 using a semi‐structured interview guide. The audio‐recorded interviews were transcribed verbatim and analysed manually using content analysis. Results The data analysis resulted in two main categories: Implementation and practices in preventing malnutrition and Challenges in working with prevention of malnutrition. Education was considered an important and essential preventative intervention. Healthcare professionals faced challenges in their work in relation to socio‐cultural and climate factors. The findings indicate how healthcare professional identified the need for increased knowledge and resources in the community to promote nutritional health in children.